4x-18=7x+6

Simple and best practice solution for 4x-18=7x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-18=7x+6 equation:


Simplifying
4x + -18 = 7x + 6

Reorder the terms:
-18 + 4x = 7x + 6

Reorder the terms:
-18 + 4x = 6 + 7x

Solving
-18 + 4x = 6 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
-18 + 4x + -7x = 6 + 7x + -7x

Combine like terms: 4x + -7x = -3x
-18 + -3x = 6 + 7x + -7x

Combine like terms: 7x + -7x = 0
-18 + -3x = 6 + 0
-18 + -3x = 6

Add '18' to each side of the equation.
-18 + 18 + -3x = 6 + 18

Combine like terms: -18 + 18 = 0
0 + -3x = 6 + 18
-3x = 6 + 18

Combine like terms: 6 + 18 = 24
-3x = 24

Divide each side by '-3'.
x = -8

Simplifying
x = -8

See similar equations:

| 9n-35=3n-9 | | (6m-7)(2m+12)=0 | | 3x+52-21=14 | | 7+65x=39x+19 | | 0.5Q-p=0 | | x+(x+1)+(x+2)=2(x+2)+1 | | (3h-7)(5h+4)=0 | | 3x+3=45x-81 | | (4k-2)(3k+6)=0 | | 0.2x+5.4=2x | | (m+11)(m-9)=0 | | 7(k-3)=k-5 | | (k+4)(3k-12)=0 | | (2x-1)*(5x+72)=250 | | (p-5)(p+2)=0 | | (p-5)(p+2)=0 | | 16t^2-49=0 | | b^2+7b+4=0 | | 5m+2=24 | | 4k=9 | | 3x+59-21=14 | | 318=10x | | 2x+y=xy | | (4y-8)(3y+7)=0 | | 100x+100=200 | | 100x-100x=212 | | 8x^3-12x^2-18x+17=0 | | 5+6x=56 | | 0.5ln+ln= | | 0.06x+0.08*(18000-x)=1290 | | 4x^4-13x^2-75=0 | | 0.5ln= |

Equations solver categories